Balanced Growth and the Two-Good, Two-Factor General Equilibrium Model - Johnson, M. Bruce (Quarterly Journal of Economics, 1961)
Journal Article Balanced Growth and the Two-Good, Two-Factor General Equilibrium Model Get access M. Bruce Johnson M. Bruce Johnson Northwestern University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 75, Issue 3, August 1961, Pages 501–505, https://doi.org/10.2307/1885139 Published: 01 August 1961